2013
DOI: 10.3389/fnhum.2013.00919
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of resting state brain networks in recovery from stress

Abstract: Chronic stress has been widely reported to have deleterious impact in multiple biological systems. Specifically, structural and functional remodeling of several brain regions following prolonged stress exposure have been described; importantly, some of these changes are eventually reversible. Recently, we showed the impact of stress on resting state networks (RSNs), but nothing is known about the plasticity of RSNs after recovery from stress. Herein, we examined the “plasticity” of RSNs, both at functional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…The few previous studies investigating the effect of stress on DMN point to a generalized increase of FC under prolonged stress conditions (Soares et al 2013a, b; Vaisvaser et al 2013). In this study, and in line with our previous findings in young participants, an increased FC in the more stressed participants (that is, higher PSS scores) was found in the DMN, suggesting augmented self-reflective thoughts and emotional processing (Soares et al 2013a).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The few previous studies investigating the effect of stress on DMN point to a generalized increase of FC under prolonged stress conditions (Soares et al 2013a, b; Vaisvaser et al 2013). In this study, and in line with our previous findings in young participants, an increased FC in the more stressed participants (that is, higher PSS scores) was found in the DMN, suggesting augmented self-reflective thoughts and emotional processing (Soares et al 2013a).…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, most of these maladaptive structural and functional responses to increased chronic stress were reported in young and middle-aged subjects and were in part shown to be reversible (Bian et al 2012; Soares et al 2012; Sousa et al 2000). Moreover, we have recently shown that stressed subjects present increased activation of the DMN, associated with impairments in the deactivation pattern and paralleled by a network volumetric atrophy (Soares et al 2013a) that is recovered after a stress-free period in young individuals (Soares et al 2013b). Emerging findings from major depression studies have pointed to altered connectivity and abnormal deactivation patterns in the DMN.…”
Section: Introductionmentioning
confidence: 99%
“…These CPS findings are of translational interest, given that FCs within and between regions comprising the DMN, namely cingulate, prefrontal, parietal and temporal cortices, are also increased in humans in states of chronic stress or depression (Broyd et al, 2009;Grimm et al, 2009;Soares et al, 2013;Whitfield-Gabrieli and Ford, 2012). Connectivity within the human DMN is proposed to relate to self-absorption and rumination.…”
Section: Increases In Within-and Between-network Functional Connectivmentioning
confidence: 90%
“…For example, the default mode network (DMN), involving cingulate, prefrontal, parietal and temporal cortices (Broyd et al, 2009), is proposed to relate to self-absorption and rumination. In fact, FC within the DMN is increased by stress (Soares et al, 2013) and in depression (Grimm et al, 2009;Whitfield-Gabrieli and Ford, 2012). In addition to these analyses of the changes in brain function underlying depression, region-specific metabolic changes as derived from MRS have been reported for depressed patients (Hasler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged stress exposure in medical students i.e. leads to functional changes in several large-scale brain networks67. High stress as induced via presentation of highly aversive visual stimuli combined with a pharmacological intervention (β-adrenergic receptor blockade via propranolol) results in profound changes of interconnectivity within the salience network (SN).…”
mentioning
confidence: 99%